2007
DOI: 10.1111/j.1468-2958.2007.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Communication Processes That Mediate Family Communication Patterns and Mental Well-Being: A Mean and Covariance Structures Analysis of Young Adults From Divorced and Nondivorced Families

Abstract: In this study, demand/withdraw patterns and feeling caught were tested as mediators of family communication patterns and young adults' mental well-being. Participants included 567 young adults from divorced and nondivorced families. For young adults in nondivorced families, family conversation orientations had both a positive, direct effect on mental well-being and an indirect effect on well-being through witnessing marital demand/withdraw patterns and feeling caught. For young adults in divorced families, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 62 publications
7
56
1
2
Order By: Relevance
“…As a limitation, the scale of revised family communication patterns in the current study had lower reliabilities than in previous studies using this scale (e.g., Ritchie & Fitzpatrick, 1990;Schrodt & Ledbetter, 2007). At this point, it is uncertain whether the scale needs improvement or whether the lower reliabilities in the current study were simply due to sampling error.…”
Section: Limitations and Directions For Future Studiescontrasting
confidence: 75%
See 1 more Smart Citation
“…As a limitation, the scale of revised family communication patterns in the current study had lower reliabilities than in previous studies using this scale (e.g., Ritchie & Fitzpatrick, 1990;Schrodt & Ledbetter, 2007). At this point, it is uncertain whether the scale needs improvement or whether the lower reliabilities in the current study were simply due to sampling error.…”
Section: Limitations and Directions For Future Studiescontrasting
confidence: 75%
“…Young adults who grew up in families with higher conversation orientation were more likely to indicate greater communication competence skills in their interpersonal relationship with others (Koesten, 2004). Additionally, research has shown that the two types of family communication patterns were differentially related to young adults' mental well-being (Schrodt & Ledbetter, 2007) and young adults' relational maintenance behaviors (Ledbetter, 2009).…”
Section: Family Communication Patternsmentioning
confidence: 99%
“…Higher scores represented more frequent mental health symptoms, and thus, poorer mental health. Again, the validity and reliability of the mental health symptom scale is well established (Dornbusch et al, 1991;Schrodt & Afifi, 2007;Schrodt & Ledbetter, 2007), and in this study, the scale produced alpha coefficients of .83 and .82 for parents and stepparents respectively.…”
Section: Mental Healthmentioning
confidence: 89%
“…Take, for example, recent empirical evidence documenting children's feelings of being caught between parents in stepfamilies (i.e., Afifi, 2003;Afifi & Schrodt, 2003a;Amato & Afifi, 2006;Braithwaite, Toller, Daas, Durham, & Jones, 2008;Schrodt & Afifi, 2007). One of the conclusions drawn from this work is that despite similarities in the processes that foster triangulation, children from postdivorce families (including stepfamilies) continue to report higher levels of feeling caught than children in first-marriage families (Schrodt & Afifi, 2007;Schrodt & Ledbetter, 2007).…”
Section: Theoretical Perspectivementioning
confidence: 91%